2019
DOI: 10.1038/s41374-018-0162-0
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect and mechanism of IL-10 on renal ischemia–reperfusion injury

Abstract: Interleukin (IL)-10, a cytokine with anti-inflammatory effects, is produced by blood cells and cells of various organs. Ischemia-reperfusion injury (IRI) is a systemic inflammatory disease caused by a systemic circulation of pro-inflammatory cytokines and chemokines produced from blood cells or organs damaged by ischemia. Apoptosis, a key event after IRI, is correlated with the degree of injury. Here we investigated the effects and mechanism of IL-10 in renal IRI. Compared to wild-type (WT) mice with a renal I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 41 publications
(42 reference statements)
1
47
0
Order By: Relevance
“…In a mouse model of acute kidney injury (AKI), our findings indicated that IL-18Rα may mediate anti-inflammatory responses through SOCS1 and/or -3 in cisplatin-induced AKI [19]. Our later investigation showed that IL-18Rα also mediates apoptosis in a murine model of ischemia/reperfusion injury [21]. In a mouse model of lupus (autoimmune nephritis), we observed that MRL-Faslpr mice (well known as a lupus model) cross-bred with mice deficient in IL-18Rα had a better survival rate and lessened nephritis because of their reduced levels of autoantibodies [15].…”
Section: Discussionmentioning
confidence: 81%
“…In a mouse model of acute kidney injury (AKI), our findings indicated that IL-18Rα may mediate anti-inflammatory responses through SOCS1 and/or -3 in cisplatin-induced AKI [19]. Our later investigation showed that IL-18Rα also mediates apoptosis in a murine model of ischemia/reperfusion injury [21]. In a mouse model of lupus (autoimmune nephritis), we observed that MRL-Faslpr mice (well known as a lupus model) cross-bred with mice deficient in IL-18Rα had a better survival rate and lessened nephritis because of their reduced levels of autoantibodies [15].…”
Section: Discussionmentioning
confidence: 81%
“…In this study, we found the numbers of inflammatory cells were suppressed in apelin-treated mice at day 1. It has been reported that IL-10, bFGF and TGF-β prevent tissue damage after I/R injury [38][39][40] . We demonstrated that qPCR analysis revealed that apelin administration enhanced the expression of these tissue protective cytokines and growth factors, such as IL-10, bFGF and TGF-β in I/R site, however, further studies will be needed to clarify the precise mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Many lung transplant recipients receive IL-2R blockade during induction therapy, which may be deleterious to outcomes as it may inhibit the ability of Tregs to facilitate tolerance induction. 171 In a pilot trial of early IL-10 therapy following human kidney transplantation, IL-10 therapy was found to be safe and associated with a reduction in TNF-α. IL-10, for example, is known to induce Foxp3 expression and Treg formation in both humans 169 and mouse models of disease.…”
Section: Future D Irec Ti On Smentioning
confidence: 99%
“…170 While the effects on IL-10 on Tregs posttransplantation remains unknown, it has been shown to suppress the release of proinflammatory cytokines and ischemia-reperfusion injury in a mouse model of kidney transplantation. 171 In a pilot trial of early IL-10 therapy following human kidney transplantation, IL-10 therapy was found to be safe and associated with a reduction in TNF-α. 172 Interestingly, methods have been developed that allow for IL-10 localization to inflamed tissues which holds great relevance in the setting of acute rejection episodes; this therapy is undergoing Phase 2 trials in rheumatoid arthritis.…”
Section: Future D Irec Ti On Smentioning
confidence: 99%